Project-Based Learning as a Catalyst for Enhanced Student Achievement in Social Studies at Islamic Junior High School - Eka Yuliana Rahman; Amri Dhimas Maulana (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to examine and analyze the effectiveness of the Project-Based Learning in improving students' academic achievement in social studies subjects in Madrasah Tsanawiyah Zainul Hasan 4 Boto Lumbang, Probolinggo Regency, as well as explore how Project-Based Learning can be integrated with Islamic values in the educational environment. Methodology: This research uses a qualitative approach with a case study design to understand how Project-Based Learning can provide students' learning experiences and their academic outcomes. Data was collected through in-depth interviews with teachers and students, classroom observations, as well as document analysis of projects produced by students. Data were analysed using thematic analysis techniques. The results of the data analysis were compiled in the form of a comprehensive research report with descriptive and interpretative narratives. Main Findings: The results showed that the implementation of Project-Based Learning significantly improved students' engagement and their understanding of social studies materials. Teachers reported that Project-Based Learning helped students develop critical, collaborative, and creative skills, and increased their learning motivation. Students involved in the project showed better ability in analysing and applying social studies concepts in real contexts. Observations showed that the classroom atmosphere became more interactive and dynamic, with students actively participating in discussions and project presentations. Novelty/Originality of this study: This research offers novelty by integrating the application of Project-Based Learning in the context of a junior high school in a remote area, namely Madrasah Tsanawiyah Zainul Hasan 4 Boto Lumbang, Probolinggo Regency. The findings make a novel contribution by showing how Project-Based Learning can be adapted and applied effectively in a different and less accessible educational context.